Psychiatric readmissions and their association with physical comorbidity: a systematic literature review. Issue 1 (December 2017) - Šprah, Lilijana; Dernovšek, Mojca; Wahlbeck, Kristian; Haaramo, Peija
Abstract Background Comorbidity between mental and physical disorder conditions is the rule rather than the exception. It is estimated that 25% of adult population have mental health condition and 68% of them suffer from comorbid medical condition. Readmission rates in psychiatric patients are high and we still lack understanding potential predictors of recidivism. Physical comorbidity could be one of important risk factors for psychiatric readmission. The aim of the present study was to review the impact of physical comorbidity variables on readmission after discharge from psychiatric or general inpatient care among patients with co-occurring psychiatric and medical conditions. Methods A comprehensive database search from January 1990 to June 2014 was performed in the following bibliographic databases: Ovid Medline, PsycINFO, ProQuest Health Management, OpenGrey and Google Scholar. An integrative research review was conducted on 23 observational studies. Results Six studies documented physical comorbidity variables only at admission/discharge and 17 also at readmission. The main body of studies supported the hypothesis that patients with mental disorders are at increased risk of readmission if they had co-occurring medical condition. The impact of physical comorbidity variables on psychiatric readmission was most frequently studied in in patients with affective and substance use disorders (SUD). Most common physical comorbidity variables with higher probability for psychiatric readmission were associated with certain category of psychiatric diagnoses. Chronic lung conditions, hepatitis C virus infection, hypertension and number of medical diagnoses were associated with increased risk of readmission in SUD; Charlson Comorbidity Index, somatic complaints, physical health problems with serious mental illnesses (schizophrenia, schizoaffective disorder, personality disorders); not specified medical illness, somatic complaints, number of medical diagnoses, hyperthyroidism with affective disorders (depression, bipolar disorder). Co-occurring physical and mental disorders can worsen patient's course of illness leading to hospital readmission also due to non-psychiatric reasons. Conclusions The association between physical comorbidity and psychiatric readmission is still poorly understood phenomenon. Nevertheless, that physical comorbid conditions are more common among readmitted patients than single admission patients, their association with readmission can vary according to the nature of mental disorders, characteristics of study population, applied concept of comorbidity, and study protocol.